Unusual presentation of psoriasis - Shaikhah Alanazi; Nora Arafat; Walid Alghamdi (Our Dermatology Online, 2018)
Psoriasis is a widely prevalent disease, a chronic disorder with genetic predisposition and many environmental triggering factors. It has various clinical presentations. Typical lesions are recurring, chronic, scaly erythematous papules and plaques. Clinical presentation differs among patients, from those with only few localized plaques over extensors to those with generalized skin involvement. We report a 28-year-old man who presented with unusual clinical presentation of psoriasis.